1242. Safety and Immunogenicity of Novel 24-Valent Pneumococcal Vaccine in Healthy Adults. (31st December 2020) - Chichili, Gurunadh; Smulders, Ronald; Santos, Vicki; Cywin, Beth; Kovanda, Laura; Malinoski, Frank J; Sebastian, Shite; Siber, George R; Malley, Rick
Abstract: Background: Invasive pneumococcal disease (IPD) remains prevalent despite the use of conjugate vaccines over the past 20 years. Serotype replacement, limited efficacy for certain vaccine serotypes, and the incomplete coverage of disease in the elderly perpetuate the problem. Novel vaccines with broader serotype coverage are needed. To this end, a novel 24-valent pneumococcal vaccine, ASP3772, was developed based on a multiple antigen-presenting system (MAPS) platform. This platform takes advantage of the high affinity, noncovalent binding between biotin and rhizavidin to create a complex of 24 pneumococcal polysaccharides and a fusion of two pneumococcal proteins. Methods: Healthy adults aged 18-64 years were randomized into this active-controlled, observer-blinded, dose-escalation study to evaluate the safety, tolerability, and immunogenicity of ASP3772 at three dose levels compared to Prevnar13 (PCV13) (target 30 per dose group). The primary endpoints were safety and reactogenicity. Immunogenicity was evaluated secondarily by measuring serotype-specific immunoglobulin G (IgG) and opsonophagocytic activity (OPA). Results: Ninety-three subjects received ASP3772 at 1 of 3 doses and 33 received PCV13. Safety and reactogenicity were similar between the ASP3772 and PCV13 arms. Most frequently reported local reactions were tenderness and pain after injection occurring within the first 2 days. Most frequent systemic reactions were fatigue, headache, and myalgia, without a clear dose response. Treatment-emergent adverse events were few and most were mild to moderate in severity. No clinically relevant abnormalities were observed in vital signs, ECGs, and laboratory parameters. Robust IgG and OPA responses were observed for serotypes shared with PCV13, as well as serotypes unique to ASP3772. Conclusion: ASP3772 vaccine was safe, well tolerated in adults aged 18-64 years, and exhibited robust immunogenicity that extended beyond serotypes shared with PCV13. Disclosures: Gurunadh Chichili, PhD, Astellas Pharma Inc (Employee) Ronald Smulders, MD, PhD, Astellas Pharma Inc (Employee) Vicki Santos, n/a, Astellas Pharma Inc (Employee) Beth Cywin, n/a, Astellas Pharma Inc (Employee) Laura Kovanda, n/a, Astellas Pharma Inc (Employee) Frank J. Malinoski, MD, PhD, Affinivax Inc (Employee) Shite Sebastian, PhD, Affinivax Inc (Employee) George R. Siber, MD, Affinivax Inc (Consultant, Employee, Shareholder) Rick Malley, MD, Affinivax Inc (Board Member, Consultant, Employee)